PERFORMANCE OF AIR INDUCTION SPRAY NOZZLE MODELS UNDER DIFFERENT OPERATING CONDITIONS - Cunha, Joao P. A. R. da (2020)
For the successful application of phytosanitary products, it is essential to understand the spraying process well. The present work aims to evaluate the spectrum and speed of the droplets produced by different spray nozzle models with air induction, working under different operating conditions. The experiment was conducted using an entirely randomized design with five repetitions in a 3 x 3 x 3 factor scheme that incorporates three nozzle models (ADIA, AIXR, and GA), three nominal flows (0.76, 1.14, and 1.51 L min(-1)), and three operating pressures (200, 300, and 400 kPa). The spectrum and speed of the droplets were determined directly using a real-time droplet analyzer based on high-resolution image analysis. The spray nozzle model interfered with the results. The ADIA promoted Dv(0.5) (VMD) higher than AIXR and GA, reaching differences of up to 90%. The increase in pressure promoted a reduction in the droplet size; however, there was no well-defined behavior for the relationship between the flow rate and droplet size. The ADIA and AIXR gave rise to greater uniformity of the droplets in most of the evaluated conditions. The increase in pressure promoted an increase in the speed of the droplets. However, the effect of the nozzle model on this parameter was dependent on the flow.